Catalytic scandium triflate mediated the synthesis of a novel C Glycoside, 2-Hydroxy-1-[3',4'-di-O-acetyl-S'-methyl-2-deoxy-β-D-arabino-hexopyranosyl]-Naphthalene - Hasnah Osman (Pusat Penerbitan Universiti (UPENA), Universiti Teknologi MARA, 2019)
Synthesis of novel C-glycoside, 2-Hydroxy-l-[3',4'-di-O-acetyl-5'-methyl-2-deoxy-β-D-arabinohexopyranosyl]-naphthalene is achieved by the reaction of 2-naphthol with D-olivoside. The reaction is efficiently catalysed by 0.25 equivalents of scandium triflate with respect to the D-olivoside. The characterisation of the synthesised C-glycoside has been described by IR, ¹H-NMR, 13C-NMR spectroscopy, HRMS and elemental analysis.